In vivo modulation of angiogenic gene expression by acyclic nucleoside phosphonates PMEDAP and PMEG - Otová, Berta; Hrdý, Jiří; Votruba, Ivan; Holý, Antonín (Anticancer research, 2009)
Acyclic nucleoside phosphonates PMEDAP and PMEG modulate expression of selected proangiogenic genes in SD-lymphoma bearing rats. Antiangiogenic efficacy of PMEDAP is relatively weak and is manifested mainly by down-regulation of vascular endothelial growth factor (VEGF) and its receptor VEGFR detectable 24 hours after treatment. Compound PMEG (an active metabolite of the prodrug GS-9219) down-regulates selected proangiogenic genes EGF, FGF, PDGF, VEGF, EGFR, FGFR, PDGFR and VEGFR much more efficiently. Its antiangiogenic potency persists and is more intensive 48 hours after treatment. Findings show that in vivo antitumour efficacy of both antimitotic acyclic nucleoside phosphonates PMEDAP and PMEG consequently affect the angiogenesis in T-cell lymphoma.
Keywords: patologická angiogeneze; Gene Expression Regulation, Neoplastic; RNA, Messenger; fibroblastový růstový faktor 1; Vascular Endothelial Growth Factor Receptor-1; Male; Platelet-Derived Growth Factor; Guanine; potkani Sprague-Dawley; Adenine; Receptor, Fibroblast Growth Factor, Type 1; organofosforové sloučeniny; regulace genové exprese u nádorů; receptor 1 pro vaskulární endoteliální růstový faktor; adenin; Receptor, Platelet-Derived Growth Factor beta; mužské pohlaví; Epidermal Growth Factor; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; Fibroblast Growth Factor 1; Lymphoma, T-Cell; receptor fibroblastových růstových faktorů, typ 1; krysa rodu Rattus; guanin; Animals; růstový faktor odvozený z trombocytů - receptor beta; Organophosphorus Compounds; destičkový růstový faktor; zvířata; Neovascularization, Pathologic; Rats; Reverse Transcriptase Polymerase Chain Reaction; lymfom T-buněčný; vaskulární endoteliální růstový faktor A; Vascular Endothelial Growth Factor A; ErbB Receptors; erbB receptory; epidermální růstový faktor; Rats, Sprague-Dawley